K-Pop and Buying Behavior: A Study of Self-Regulation on Students' Purchase Intention in a K-Pop Era - Sania Rahmah, Febi; Dharmastuti, Anjarie; Setyo Pambudi, Kukuh; Tania, Basma; Mutia Rahmah, Bintang (Ilomata International Journal of Social Science, 2025)
Indonesia has now entered the era of globalization. The era of globalization is when each country's culture blends into a global culture. One of the popular cultures favored in Indonesia is Korean POP culture. The purpose of this study is to determine the relationship between self-regulation and purchase intention for products advertised by K-Pop artists among students. The population in this study consists of K-Pop fan students. The sample used in this research was 105 students. The sampling technique used was purposive sampling. There were two instruments used in this study. First, the Short Self-Regulation Scale (SSR), which consists of nine question items, developed by Tresnadiani and Taufik (2020). Second, a scale adapted from the product purchase intention scale for Honda products developed by Wicaksono (2015), which consists of eight question items. These two scales were distributed through various social media platforms to collect research data. After collecting the research data, the data were analyzed using parametric analysis, with hypothesis testing using the Spearman correlation test. Data analysis was conducted using SPSS version 26. The results of the Spearman correlation test showed a significance value in the Sig. (2-tailed) section of 0.002 (0.002 < 0.05), indicating that there is a relationship between self-regulation and purchase intention for products advertised by K-Pop artists. The Pearson correlation result was 0.302, meaning the strength of the relationship is considered weak. The weak relationship indicates that the products advertised by K-Pop idols do not always attract the purchasing interest of K-Pop fans to buy those products. Instead, there are other factors that can influence purchasing interest, such as product quality, packaging, and price.